OVERLAY THICKNESS ANALYSIS OF FLEXIBLE PAVEMENT ON ROAD MAINTENANCE PROGRAM (CASE STUDY: CIREBON ROADSâBORDER OF KUNINGAN REGENCY) - Dwiriani R, Theresia
Destruction of road assets due to overloading, climate, high temperatures, and subgrade conditions. The budget constraint is also an obstacle in the road maintenance program. An approach is needed to plan overlay thickness on flexible pavement structures using the 1993 AASHTO method and the MDP 2017 mechanistic-empirical method with KENPAVE software to prevent damage to the flexible pavement structure before the design life and carry out a maintenance program to control the budget that will be spent when handling overlays. This study aims to compare the overlay thickness and then develop 3 road maintenance scenarios for both methods. Based on the AASHTO 1993 method, the FWD deflection analysis results at the Cirebon Roads-Border of Kuningan Regency with a path length of 12.16 km, the uniformity factor (FK) of 34.35 %, then it is necessary to make a segmentation that is divided into 5 segments to achieve uniformity. Furthermore, the representative deflection value (dwakil) in each segment is used the back calculation to determine the value of the subgrade modulus of resilience (MR) and the effective pavement modulus (Ep) of the existing pavement structure. LHR data results in average traffic growth in 2015-2017 = 4.47% with 10 years of design life, and CESAL's calculation used the VDF value of MDP 2017 = 42,706,076 ESAL. Using the mechanistic-empirical MDP 2017 method, LHR 2022 data = 44,657 vehicles, HV% = 6.79% with 10 years of design life and average axle load of the vehicle (NHVAG = 2.8), the result of the design traffic (NDT) is 19.025.192 ESA/HVAG. The NDT value multiplied by the value of the traffic multiplier (TM) as a correction for fatigue crack damage (TM = 1,1) = 20.927.711 SAR5/ESA and permanent deformation (TM = 1,6) = 30.440.307 SAR7/ESA. The result of overlay thickness using the AASHTO 1993 method is Segment 2 for Scenario 1: full overlay = 18 cm; Scenario 2: 5 cm overlay thickness per year = 20 cm; and Scenario 3: if the budget is limited = 15 cm due to the resilience of modulus subgrade (MR) in Segment 2 is lower than other segments. The result of overlay thickness using mechanistic-empirical MDP 2017 method is Segment 3 for Scenario 1: full overlay = 27 cm; Scenario 2: 5 cm overlay thickness per year = 10 cm; and Scenario 3: if the budget is limited = 9 cm due to the effective modulus of pavement (Ep) in Segment 3 has lower of stiffness than other segments. The highest cost of road maintenance under the AASHTO 1993 method is Scenario 2 and the lowest cost is Scenario 1. Based on the mechanistic-empirical MDP 2017 method, the lowest cost is Scenario 3, and the highest cost is Scenario 1.